SEJARAH DAN DINAMIKA PIMPINAN CABANG MUHAMMADIYAH KEBAYORAN BARU - Mukhlish Muhammad Maududi; Mohammad Supendi (Ekonomi Islam, 2020)
Muhammadiyah Kebayoran Baru Branch is one of the oldest branches in Jakarta, with a well-developed Charity Business, such as Leading Schools and Hospitals and the success of organizing da'wah, is also the place for the establishment of the Muhammdiyah Vigilance and Preparedness Command "abbreviated as KOKAM. This research is intended so that the next generation can listen, follow, and understand how Muhammadiyah was born, grew, developed and survived until now. The method used is qualitative research with secondary data collection techniques by extracting information from documents or electronic sources. In collecting data the observations are first performed, tracing documents related to the Branch Manager of Muhammadiyah Kebayoran Baru. Data analysis was performed after obtaining secondary data with qualitative descriptive methods.